Evaluación de la formación sobre el programa de optimización del uso de antimicrobianos en médicos residentes de la provincia de Las Palmas. - de Arriba-Fernández, Alejandro; Jesús Molina-Cabrillana, Manuel; Hernández-Aceituno, Ana; José García-López, Fernando (Revista Española de Quimioterapia, 2020)
Background. Antibiotic resistance is a threat to global public health. This situation makes essential to establish programs to optimize antimicrobial use (PROA). Training needs are identified in the PROA of resident physicians and the results of the analysis of the associations between study variables and training in the rational and prudent use of antibiotics are presented in this analysis. Methods. Cross-sectional and analytical study through a self-administered questionnaire to a group of 506 medical residents of the province of Las Palmas. The association between resident's characteristics and PROA training was calculated through logistic regression. Results. The associations between response variance and speciality were observed in most of the core component analysis (opportunity p=0.003, training p=0.007, motivation p=0.055 and hand hygiene p=0.044), followed by variance according to sex (capacity p=0.028, theoretical knowledge p=0.013, hand hygiene p=0.002). Very few differences were associated with age (capacity p=0,051 and hand hygiene p=0,054) or the year of expertise (hand hygiene p=0,032). Conclusions. The main training needs of resident physicians include one health, motivation, training, hand hygiene and information. The type of speciality followed by sex are the most important determinants on antibiotic use and resistance for resident physicians.